KAJIAN LITERATUR: PERAN EMPATI DALAM PENCEGAHAN TINDAKAN BULLYING DI LINGKUNGAN SEKOLAH DASAR - M. Ajmul Nashir; Alfisyah; Najma Khairina; Rusyifa Aina Hayati; Ahmad Suriansyah; Wahdah Refia Rafianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Bullying in elementary school settings remains a serious issue that significantly affects students’ social, emotional, and academic development. Numerous studies indicate that low levels of empathy among perpetrators are closely associated with a higher tendency toward bullying behavior; however, gaps remain in understanding how empathy can be effectively developed and implemented as a preventive strategy in elementary education. Therefore, this article aims to comprehensively examine the role of empathy as a protective factor in preventing bullying and to identify relevant and contextual strategies for empathy development in elementary schools. This study employed a literature review method by analyzing national and international scholarly journals, academic books, and conference proceedings published between 2020 and 2025, accessed through databases such as Google Scholar, Sinta, and Garuda. The collected data were analyzed using descriptive qualitative analysis by synthesizing key findings related to the concept of empathy, characteristics of bullying, and empathy-based interventions in elementary school contexts. The findings indicate that empathy particularly in the dimensions of perspective-taking, affective concern, and social response plays a significant role in reducing bullying behavior and fostering a safe and inclusive school social climate. Empathy-based prevention strategies are found to be more effective when systematically integrated into the curriculum, school culture, and daily instructional practices. This review underscores the importance of strengthening social-emotional learning in elementary education and recommends the development and empirical testing of measurable and context-sensitive empathy intervention models for future research.